The Effect of Using Small Group Discussion (SGD) on Students’ Analytical Exposition Text Writing - Rizki, Lutfika; Indrayani, Ninuk (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2024)
This research investigated the effect of SGD on students’ analytical exposition text writing for eleventh graders in SMAN 1 Srono. This research employed experimental research in two classes, those were XI IPA 1 as experimental class and XI IPS 2 as control class. XI IPA 1 class consists of 34 students and XI IPS 2 class consists of 33 students. Both of class were given pretest, treatment, and post-test. In this research, the researcher was giving same material but different treatment. The experimental class was tough with applied SGD as the method while the control class was tough without applied SGD. The result of this research showed that the experimental class was got higher score than control class in the post-test. The mean score of post-tests in the experimental class was 84,17 while in the control class was 68,30. Then, the researcher used independent sample t-test using SPSS 28 to test the hypothesis. The result of independent sample t-test showed the significant value was <0,001 which lower than significant level 0,05. Thus, the researcher concluded that there was an effect of using small group discussion on students’ analytical exposition text writing.